Understanding the Redox Reaction of Self-Assembled Ferrocence-Containing Polymer Particle Comprising Ferrocenylmethyl Methacrylate–Methacrylic Acid Random Copolymers. Issue 13 (12th October 2020) - Lee, Semi; Na, Yoonhee; Seol, Kang Hee; Il Choi, Won; Sung, Daekyung; Chang, Jinho
Abstract : In this study, the electrochemistry of Ferrocene-containing polymer particles (Fc-PPs) dispersed in an aqueous solution is investigated owing to the importance of Fc in drug-delivery systems, wherein drug release is triggered by reactive oxygen species (ROS). The mechanism of Fc + /Fc redox reaction in an aqueous solution containing Fc-PP was evaluated, where Fc-PP was self-assembled from Fc-containing polymers (Fc-Ps) synthesized via random copolymerization of ferrocenylmethyl methacrylate (FMMA) and methacrylic acid (MA). The cyclic voltammogram (CV) of the aqueous solution containing Fc-PP on a Pt ultramicroelectrode (UME) was sigmoidal, which is the typical shape observed when dissolved redox-active species are electrochemically oxidized or reduced under mass-transfer controlled conditions. Chronoamperometric analysis of the reaction of Fc-PP dispersed in solution on the Pt UME showed no stochastic current spikes associated with the direct electro-oxidation of Fc to Fc + in the Fc-PP via collision. The absence of stochastic current spikes mainly resulted from slow e ‒ transport through Fc-PP, which indicates its nature as an e ‒ insulator. Thus, the voltammetric current was not directly attributed to the electrochemical redox reaction of Fc-PP on the Pt UME. It is proposed that the Faradaic current can be attributed to Fc-P species that were slightly dissociated from Fc-PP at equilibrium, where the former have a higher degree of freedom in the aqueous phase, which promotes facilitated e ‒ transport from Fc-P to Pt UME or vice versa. Finite element analysis based on this model adequately explained the experimentally obtained voltammetric curves. From the simulation, redox-active Fc-P possibly reacted with Fc-PP via galvanic exchange, resulting in a catalytic loop and consequent current amplification. Nonetheless, the data revealed that this catalytic current induced by the galvanic exchange reaction would not be significant. The electrochemical analyses strongly indicate that charge transfer between Fc in Fc-PP and ROS (such as H2 O2 ) would be the main rate determining step for the drug-release system, as previously reported ( J. Mater. Chem. B 2020, 8, 1906).